2015
DOI: 10.4414/smw.2015.14226
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive improvement in patients with carotid stenosis is independent of treatment type

Abstract: Treatment of carotid artery stenosis decreases the long-term risk of stroke and may enhance cerebral blood flow. It is therefore expected to have the potential to prevent cognitive decline or even improve cognition over the long-term. However, intervention itself can cause peri-interventional cerebral infarcts, possibly resulting in a decline of cognitive performance, at least for a short time. We investigated the long-term effects of three treatment methods on cognition and the emotional state one year after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
0
12
0
5
Order By: Relevance
“…In the studies where changes in cognitive function in a year after CEA or CAS versus the control group was assessed with the MoCA test, the results indicated that cognitive function might improve or at least do not decline in symptomatic and asymptomatic elderly patients with severe carotid stenosis who had revascularisation [40, 41]. Comparing studies where long-term effects of different carotid stenosis treatment methods (CEA, CAS or BMT) on cognitive function were assessed, their results also show that revascularisation of carotid stenosis improves long-term cognitive performance, independent of treatment type [42-46]. Except, older studies have suggested that there is no difference between cognitive function before and after carotid stenosis revascularisation (CEA, CAS) [47, 48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies where changes in cognitive function in a year after CEA or CAS versus the control group was assessed with the MoCA test, the results indicated that cognitive function might improve or at least do not decline in symptomatic and asymptomatic elderly patients with severe carotid stenosis who had revascularisation [40, 41]. Comparing studies where long-term effects of different carotid stenosis treatment methods (CEA, CAS or BMT) on cognitive function were assessed, their results also show that revascularisation of carotid stenosis improves long-term cognitive performance, independent of treatment type [42-46]. Except, older studies have suggested that there is no difference between cognitive function before and after carotid stenosis revascularisation (CEA, CAS) [47, 48].…”
Section: Discussionmentioning
confidence: 99%
“…Except, older studies have suggested that there is no difference between cognitive function before and after carotid stenosis revascularisation (CEA, CAS) [47, 48]. However, comparing the treatment effect of carotid stenosis in older studies, the results of these studies must be interpreted with caution because in recent decades not only pharmacological management of cerebrovascular disease but also the technical equipment and skills of revascularisation have been improved [42].…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of these risk factors was similar between the experimental and control groups, they may have influenced cognitive performance in our study, thus the sole impact of severe CAS on cognition may be affected or left obscure. Nevertheless, these data could be considered because, besides being the best medical treatment for CAS, revascularisation may not only prevent risk of stroke but also improve [ 42 - 44 ] or provide some protection against cognitive decline in the elderly [ 31 ], [ 45 ]. When the results of our study are compared with other studies that used MoCA as a screening tool to assess cognitive performance [ 45 ], [ 46 ], there were some slight discrepancies, which may be due to disparities in the quantification of CAS and calculation of mean MoCA scores.…”
Section: Discussionmentioning
confidence: 99%
“…Further, several studies investigated on variations in cognitive performance using clinical neuropsychological tests, demonstrating that CAS [7,8] and CEA [9] are associated with increasing in cognitive performances, and these improvements are independent from the treatment type (CEA vs CAS) [10]. Resting State Functional Connectivity Magnetic Resonance (rs-fcMR) allows to study the spontaneous brain networks' activity while patient lies inactive in MR scanner, analyzing Blood Oxygenation Levels Dependent (BOLD) signal fluctuation generated by local changes of deoxyhemoglobin levels of the active brain regions following their activation [11].…”
Section: Introductionmentioning
confidence: 99%